In vitro experimental investigation of the forces and torque acting on the scaphoid during light grasp. Issue 10 (2nd February 2016) - Erhart, Jochen; Unger, Ewald; Schefzig, Philip; Krumboeck, Anna; Hagmann, Michael; Vecsei, Vilmos; Mayr, Winfried
ABSTRACT: The aim of this study was to measure the magnitude and direction of forces and torque within osteotomized scaphoids within cadaveric wrists during grasping movement of the hand. The mechanical contributions of clinically relevant individual wrist‐crossing tendon groups were investigated. Wrists of eight forearms were immobilized in the sagittal, transverse, and coronal plane on a fixation device with unhindered axial gliding. The scaphoid was osteotomized and the fragments stabilized using an interlocking nail. The nail served as a sensor for measurement of inter‐fragmentary forces orthogonal and torque around the sensor axis. Thus, torque and cantilever forces were measured which originated between the fragments through co‐contraction through the activity of wrist‐crossing tendons. Grasping movement of the hand induced a mean maximum torque of 0.038 ± 0.051 Nm and a force of 4.01 ± 1.71 N on the scaphoid. The isolated activation of thumb tendons resulted in a torque of 9.9 E −3 ± 7.7 E −3 Nm and a force of 1.42 ± 0.49 N. Despite immobilization of the wrist, grasping movement of the hand caused substantial forces and torque within the osteotomized scaphoid bone in varying directions and severity among different specimens. These factors may contribute to the development of nonunions and malunions in unstable scaphoid fractures through interfragmentary micromotion. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1734–1742, 2016.